Examination of non-traditional wax management techniques for flow assurance in petroleum production - Bassey, Bassey O.; Verdin, Patrick G.; Lao, Liyun (Society of Petroleum Engineers (SPE), 2022)
Wax deposition and build-up in reservoirs, wells and pipelines negatively impact asset productivity, integrity and economics. Several flow assurance techniques have been developed to mitigate or remediate waxing problems. Prominent among these are controlling operating conditions, chemical, thermal and mechanical methods. Their major drawbacks have remained exorbitant costs over life-of-field, no single method being sufficient, risk of costly mistakes due to overdesign or underdesign, etc. Some innovative, unconventional solutions were also developed over the past 2 decades, with promising results, though mostly yet to be commercialised. This paper highlights and reflects upon these hitherto standalone technologies given the largely sparse treatise they have received in the literature. The aim is to explore alternative wax management techniques as a means of improving the science of wax deposition and dissolution. Non-traditional methods were critically examined during a 12-month extensive literature survey. In-depth study of the rationale, principle of operation, results obtained, advantages and limitations of each method was performed. Independent studies using variants of the same method were juxtaposed to ascertain similarities and differences in applicability, with meeting points established to pave the way for future research collaboration. Reflections upon their merits, limitations, areas for improvement, and a case for scale-up are presented. Some non-traditional techniques have overcome certain perennial constraints of conventional techniques widely used in industry. The wax inhibition tool, for example, has low energy requirements, causes minimal environmental impacts and has relatively low costs. The precious metals and quartz used in making the tool are available locally, the alloys were mixed in the university's materials laboratory using in-house manpower and the flow loop was locally designed and fabricated. Having developed expertise on this project through repeat and improved experiments, preparing and implementing a cost-effective work program for its commercialization is doable by the research group with industry partnership. Adapting oscillatory motion based on Avrami theory to understand mechanism and kinetics of wax crystallization by experiments on North Sea crude had yielded two opposite effects that are interesting to note. Repeat experiments a decade later using synthetic oils from Southeast Asia yielded improved results and better understanding of wax deposition kinetics; an indication that this topic holds promise to unravel some mysteries in the subject, if its deliverables are embraced and implemented. The expose provided by this paper will hopefully contribute towards available knowledge on wax management. It is expected that conscious follow up on these technologies, some of which are related and could be hybridized, would inform future research directions for both the academia and industry in the field of flow assurance.
Keywords: Wax deposition; non-traditional methods; bench scale; research collaboration; petroleum production systems